Status of Antibiotic Residues in Poultry Meat of Nepal - Prajapati, M.; Ranjit, E.; Shrestha, R.; Shrestha, S.P.; Adhikari, S.K.; Khanal, D.R. (Nepalese Veterinary Journal, 2018)
Antibiotic residues in livestock products are the burning issue in animal production as well as public health sector. Imprudent use of antibiotics in poultry production increases the risk of antibiotic resistance thus increasing risk in both animals and humans. To determine the trend of antibiotic residues presence in poultry meat, a study was conducted from June 2016 to May 2017 in Kathmandu, Kaski, and Chitwan districts of Nepal. A total of 92 breast samples of broilers ( Kathmandu-30, Kaski-40 and Chitwan-22) were collected randomly from different selling outlets of the study areas and tested for residues of commonly used antibiotic viz. Enrofloxacin (EX), Ciprofloxacin (CIP), Streptomycin (STR) and Chloramphenicol (CHL) using the Enzyme Linked Immunosorbent Assay (ELISA) technique. Out of 92 samples, 57 (62%) samples were found positive for antibiotics residue of which 38% samples were positive for STR residue, 15.2% for CIP and 8.7% for EX. However, none of the samples showed positivity for CHL residue. The level of STR was determined to be higher in all districts in comparison to other antibiotics. The meat samples from Kaski were found to contain higher level of STR (56.1%) while highest percentage of CIP (16.1%) was detected in Kathmandu. Also, presence of EX was found highest in Kathmandu compared to other districts. The study concluded that antibiotics residues have been abundantly found in poultry meat which can have serious effect in human health. Hence, to mitigate this, routine antibiotics residues monitoring and surveillance programmes in food animal products should be conducted to ensure the consumer safety.